G0.5 PAMAM dendrimers improve the kinetic stabilization and nanoscale precipitation mechanism of amorphous calcium carbonate. Issue 71 (21st September 2017) - Shi, Weiguang; Ma, Zaiqiang; Mu, Yuqiang; Wang, Jun; Li, Benxian; Wang, Xiaofeng; Teng, Zhaogang; Liu, Xiaoyang
Abstract : Multiple functions of G0.5 PAMAM stabilize the kinetics process of ACC nucleation and its nanoscale precipitation mechanism. Abstract : A series of nanoscale amorphous calcium carbonate (nano-ACC) precipitates are prepared by alternating the concentration of carboxylic acid-terminated G0.5 poly(amidoamine) dendrimer with a CaCl2 –Na2 CO3 liquid–liquid phase which acts as a nucleation site at a fixed initial pH of 12 ± 0.2 at 15 °C. Analysis of the reaction time and particle size shows a four stage ACC precipitation mechanism including a combination of primary nucleation, secondary nucleation and diffusion controlled fast and slow growth, which is proved by electrical conductivity (EC) experiments. Moreover, the crystallization of calcite via vaterite is investigated. It is found that the stabilization of ACC and delay of the transformation from ACC to calcite via vaterite in aqueous systems is due to the surface activity and dendritic effect of G0.5, which have a significant effect on the kinetic process of the ACC nucleation stage.